Calculations of quantum oscillations in quasi-two-dimensional charge-transfer salts - Singleton, J; Harrison, N; Bogaerts, R; Reinders, P; Deckers, I; Blundell, S; Herlach, F (1997)
A numerical model is used to derive the quantum oscillations in the magnetisation and magnetoresistance of quasi-two-dimensional alpha-phase BEDT-TTF charge-transfer salts in high magnetic fields. Recent experimental results are simulated and the standard Lifshitz-Kosevich formalism is shown to be no longer appropriate.